Background modeling and foreground detection for video surveillance - Bouwmans, Thierry; Porikli, Fatih; Hoferlin, Benjamin; Vacavant, Antoine (Chapman & Hall/CRC, 2014)
Incorporating both established and new ideas, this book provides a complete overview of the concepts, algorithms, and applications related to background modeling and foreground detection. Leaders in the field address a wide range of challenges, including camera jitter and background subtraction.